PENGETAHUAN YANG CUKUP TENTANG IUD BERDASARKAN TINGKAT PENDIDIKAN DAN SUMBER INFORMASI PADA AKSEPTOR IUD PUSKESMAS I KEMBARAN - Tin Utami; Sinta Indah Wati (Viva Medika, 2009)
The tendency of contraceptive use in Indonesia is not based on a considerationrationalistic, effectiveness and efficiency. Based on the preliminary surveyconducted in Puskesmas I Kembaran Banyumas, turns acceptors said they did notknow much about family planning methods they use, they merely know about itsusefulness, which is to delay pregnancy. The purpose of this study was todetermine the level of knowledge about the IUD IUD acceptors in Puskesmas IKembaran Banyumas Month Period from March to July 2010 based on the levelof education and resources. This type of research is descriptive research withcross sectional approach. The population in this study are all family planningacceptors in Puskesmas I IUD Kembaran Banyumas regency period January toMay 2009 amounted to 118 acceptors. By sampling a total of sampling as manyas 118 acceptors. The results showed that the level of knowledge about the IUDIUD acceptors largely in enough categories, and a small portion in the poorcategory. Acceptors educated elementary, junior and senior high schools mostlyhave the level of knowledge about the IUD in the category enough. While therespondents to D3 or PT mostly have this level of knowledge in both categories.IUD acceptors who get information about the IUD most widely obtain resourcesfrom the media. Based on the results that the level of knowledge of familyplanning acceptors in Puskesmas I IUD Kembaran Banyumas most in thecategory of pretty, by education level is junior high, resources are obtained fromthe media.Keywords: Knowledge, IUD Acceptors